EKSISTENSI RADIO VOKS 91.7 BANDUNG DI ERA DIGITALISASI INFORMASI - Ersyad Muttaqien, Muhammad; Candra, Muhammad Fazri (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2025)
Radio is a traditional medium that delivers information through audio and frequency networks. In the current media landscape, radio faces the challenge of adapting to the digitalization of information on new media platforms and providing content that resonates with today’s audience characteristics. One region where the radio industry has grown significantly and become a trendsetter is Bandung. The researcher observed one radio station, Voks Radio 91.7 FM Bandung, which employs a unique and serious approach to addressing these challenges.This study aims to explore the existence of Voks Radio Bandung in the era of digital information. The research employs a qualitative verificative analysis method, focusing on analyzing and verifying various issues, methods, and dynamics in the radio industry through an in-depth examination of information quality. The findings reveal that Voks Radio Bandung utilizes at least five key principles to develop its radio business: (1) Psychological Relief: Providing a platform that helps listeners unwind from psychological burdens. (2) Relaxation and Leisure: Offering programs that create a relaxing atmosphere, catering to listeners’ need for entertainment during leisure time. (3) Emotional Expression: Allowing listeners to interact with broadcasters and explore their favorite music live. (4) Enhanced Accessibility: Developing a comprehensive super app to facilitate better connectivity between the radio station and its audience through more user-friendly technical features. (5) Integrated Business Strategy: Leveraging its main business, “Kutus-Kutus,” as a revenue generator to support and sustain the radio station’s operations. This strategic integration enables Voks Radio to remain relevant and competitive in the digital era while catering to the evolving preferences of its listeners. Keywords: Radio, the radio industry, and the digitalization of information